Patterns and predictors of sleep disordered breathing in primary myopathies. Issue 8 (1st August 2002) - Ragette, R; Mellies, U; Schwake, C; Voit, T; Teschler, H
Abstract : Background: Sleep disordered breathing (SDB) is common in neuromuscular diseases but its relationship to respiratory function is poorly defined. A study was undertaken to identify distinct patterns of SDB, to clarify the relationships between SDB and lung and respiratory muscle function, and to identify daytime predictors for SDB at its onset, for SDB with continuous hypercapnic hypoventilation, and for diurnal respiratory failure. Methods: Upright and supine inspiratory vital capacity (IVC, % predicted), maximal inspiratory muscle pressure (Pi max), respiratory drive (P0.1 ), respiratory muscle effort (P0.1 /Pi max), and arterial blood gas tensions were prospectively compared with polysomnography and capnometry (Ptcco 2 ) in 42 patients with primary myopathies. Results: IVC correlated with respiratory muscle function and gas exchange by day and night. SDB evolved in three distinct patterns from REM hypopnoeas, to REM hypopnoeas with REM hypoventilation, to REM/non-REM (continuous) hypoventilation, and preceded diurnal respiratory failure. SDB correlated with IVC and Pi max which yielded highly predictive thresholds for SDB onset (IVC <60%, Pi max <4.5 kPa), SDB with continuous hypoventilation (IVC <40%, Pi max <4.0 kPa), and SDB with diurnal respiratory failure (IVC <25%, Pi max <3.5 kPa). Conclusion: Progressive ventilatory restriction in neuromuscular diseases correlates with respiratory muscle weakness and results in progressive SDB which, by pattern and severity, can be predicted from daytime lung and respiratory muscle function.